Gas Sorption Properties of a New Three-Dimensional In-ABDC MOF With a Diamond Net - Choi, In-Hwan; Yoon, Suk Bin; Jang, So-Young; Huh, Seong; Kim, Sung-Jin; Kim, Youngmee (Frontiers in Materials, 2019)
The pseudotetrahedral node, [In(O2CR)4]-, often found in InIII-based metal-organic frameworks (MOFs) without a cluster-based secondary building unit (SBU) is a negatively charged center due to charge mismatch between an 8-coordinate InIII ion and four anionic carboxylate bridging ligands. Thus, In-MOFs with this pseudotetrahedral node tend to bear a counter-cation near each InIII center in the frameworks. Generally, dialkylammonium-based cations such as Me2NH2+ and Et2NH2+ directly derived from N,N-dimethylformamide (DMF) or N,N-diethylformamide (DEF) solvents during MOF formation reactions play a significant role to form a stable framework through charge matching. If these cations thermally derived from DMF or DEF were not suitable for crystal growth of In-MOFs, it becomes very challenging to obtain high quality single crystals for X-ray structure determination of the frameworks. In this context, high quality crystals of In-ABDC MOF were not easily prepared from a ditopic azobenzene-4,4'-dicarboxylic acid (H2ABDC) through a thermal reaction in DMF or DEF. We successfully overcome this problem by employing a room-temperature ionic liquid, 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]), and the resulting three-dimensional (3D) In-ABDC MOF, [EMIM][In(ABDC)2]•DEF•H2O (I), was structurally characterized by X-ray diffraction. The 3D framework indicates a 4-connected uninodal net with Schläfli symbol of 66 (dia). The gas sorption properties of solvent-free I were also investigated in detail.